(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Laboratory studies were carried out with egg batches of Thaumetopoea pityocampa (Denn. & Schiff.) collected on the Peloponnes/ Greece to study why many eggs do not develop and to find out the role of the parasitoids. The investigations started when all caterpillars had hatched and lasted for about two and a half years. During this time the hatching periods of the parasitoids were recorded. All egg batches were laid on needles of Pinus halepensis Miller. From batches which had overlain one year no parasitoid hatched during the second year although many undeveloped eggs were present. Hatching of parasitoids could be observed only up to one year after egg deposition. Two hatching periods of parasitoids were observed during the first year after egg deposition. One was found in May-June for Ooencyrtus sp. and the other in September for Tetrastichus sp., the latter was synchronized with the egg laying of the host. The parasitoids developed at 22-27°C. At these temperatures only females hatched apart from one male of Tetrastichus sp.. In two egg batches more parasitoids were counted than hatching holes were present. In nature most of the diapausing parasitoids are eaten by predatory birds during winter time.